THE IMPACT OF EMOTIONAL INTELLIGENCE TOWARDS ISLAMIC RELIGIOUS EDUCATION LEARNING OUTCOMES AT JUNIOR HIGH SCHOOL STUDENTS - Elya, Elya; Naima, Naima; Nursyam, Nursyam; Rahmah, Hikmatur; Hildawati, Hildawati (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: The practice of education gives the perception that education is always centered on learning materials that require students to have cognitive and motor skills, but pay less attention to fulfilling emotions. Purpose: This study aims to investigate and analyze the impact of emotional intelligence on academic achievement in Islamic religious education among junior high school students. Method: This research uses quantitative methods using inferential analysis. The population in this study were students at SMPN 2 Sigi with a total of 277 people with a sample size of 164 students. Result: The research findings indicate a notable correlation between emotional intelligence and learning achievement in Islamic religious education subjects at SMPN 2 Sigi. This is evident through hypothesis testing where the coefficient value for the Emotional Intelligence variable is 0.760, with a standard error of 0.036, and a t-statistic value of 21.104, with a significance level of less than 0.05. Conclusion: The research concluded that emotional intelligence exhibits a significant and positive association with academic achievement in Islamic Religious Education among junior high school students.